2007
DOI: 10.3892/ijo.30.3.641
|View full text |Cite
|
Sign up to set email alerts
|

The low-toxicity 9-cis UAB30 novel retinoid down-regulates the DNA methyltransferases and has anti-telomerase activity in human breast cancer cells

Abstract: Retinoic acids and their derivatives potentiate anticancer effects in breast cancer cells. The aberrant expression of telomerase is critical to the continued proliferation of most cancer cells. Thus, telomerase is an attractive target for chemoprevention and treatment of breast cancer. 9cUAB30 is a novel synthetic retinoid X receptor-selective retinoic acid (RA) that effectively reduces the tumorigenic phenotype in mouse breast carcinoma with lower toxic effects than natural retinoid treatments. We have assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Treatment with the retinoid 9cUAB30, a synthetic analog of 9-cis-retinoic acid, leads to downregulation of hTERT expression, decrease in telomerase activity, and induction of apoptosis of leukemic cells (Love et al 2008). The compound has also demonstrated beneficial effects against breast cancer (Hansen et al 2007). These findings strongly support the use of 9cUAB30 as a chemo preventative agent.…”
Section: Retinoidsmentioning
confidence: 99%
“…Treatment with the retinoid 9cUAB30, a synthetic analog of 9-cis-retinoic acid, leads to downregulation of hTERT expression, decrease in telomerase activity, and induction of apoptosis of leukemic cells (Love et al 2008). The compound has also demonstrated beneficial effects against breast cancer (Hansen et al 2007). These findings strongly support the use of 9cUAB30 as a chemo preventative agent.…”
Section: Retinoidsmentioning
confidence: 99%
“…9-cis-UAB30 is a potential chemopreventive agent that has been shown to be effective on a number of different types of tumors (Grubbs et al, 2003;Lettinga et al, 1996;Hansen et al, 2007). The safety and toxicity testing of 9-cis-UAB30 is a necessary step for IND submission of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic component of telomerase, hTERT, is a target for anticancer therapies due to its differential expression in cancer and normally dividing cells (Hansen et al, 2007). Hansen et al reported that 9-cis-UAB30 is effective in inhibiting the growth of human breast cancer cells .…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is evidence that atRA (and other retinoids) can directly change DNMT mRNA levels (Hansen et al, 2007) and result in differential expression of DNMTs (Love et al, 2008). If RAs can directly influence DNMT levels, this would represent another retinoid-regulated epigenetic mechanism to establish heritable DNA methylation patterns.…”
Section: Retinoids and Epigenetic Mechanismsmentioning
confidence: 99%